Social entrepreneur intention: a review and research direction - Sabri, Khairun Najihah; Mohamad, Siti Fatimah; Ungku Zainal Abidin, Ungku Fatimah; Ghazali, Hazrina; Ali@Hamid, Mass Hareeza (Human Resource Management Academic Research Society, 2023)
Social entrepreneurship is a burgeoning research area that has recently garnered significant attention. Consequently, the concept of social entrepreneurial intention (SEI) has emerged as a topic of considerable interest. This paper aims to explore the factors influencing the intention to become a social entrepreneur in Malaysia. While SEI is deemed a crucial precursor to launching a social enterprise, existing empirical research on SEI factors lacks a structured and quantitatively integrated approach. Furthermore, most studies have centered on commercial enterprises rather than social ones. The dearth of research on social entrepreneurial behaviors necessitates an exploration of the critical elements that drive such behaviors and actions. A comprehensive literature review has been employed to organize existing research and establish the study's research direction, which focuses on the intentions of social entrepreneurs. This study is expected to provide insights for both society and policymakers, thereby contributing to the advancement of social entrepreneurship in Malaysia.